Bridge to Success: English for International Studies Students (Year 2) - Bohatyrets, Valentyna; Kudelko, Zoya (Технодрук, 2022)
The manual “Bridge to Success: English for International Studies Students” (Year 2) learning goals were to proceed with developing a special course of the English language for the students of International Studies aimed at teaching Ukrainian language students the peculiarities of English connected with international affairs and its usage. These goals were and remain difficult to reach, since learning English as the language of the 21st century (in particular, peculiarities of usage, grammatical forms and constructions) is complicated due to many extralinguistic factors, e.g., differences in political systems and realities, different traditions in the use of written language and paper work. Taking into consideration the above-mentioned, from the very beginning of its development this course was focused on both teaching students international English proper and providing them with the minimum of country studies necessary for that. The system of exercises has been developed to allow the lecturer to check how students are mastering both certain parts within a module and a module as a whole. The manual has been prepared on the modular basis and is divided into modules. Each module consists of the following main parts: main and supplementary texts, lexical and lexical and syntactic exercises onto these texts, exercises on the translation from English into Ukrainian and vice versa, as well as practical tests directed at examining students’ progress in mastering study materials and preparing them for the midterm and final tests. Ancillary texts offer more detailed information on certain issues related to the main topic of each module. Besides, every module also contains thematic glossaries which enable students to enrich their vocabularies on the respective topics. “Bridge to Success: English for International Studies Students” (Year 2) provides a solid foundation for students who have a minimal understanding of the English Language. Students will very quickly overcome their fear of speaking and will soon improve their listening, reading and writing skills. To achieve the level of linguistic and communicative competence that you need for daily usage as well as for higher education you are encouraged to start right now.
Шлях до успіху: Англійська мова для студентів міжнародних студій (Частина 2)
Coursebook
Keywords: English for International Studies Students; manual; розвиток мовленнєвої, лінгвальної та лінгвокраїнознавчої компетенцій